Ý định mua sắm xanh của người tiêu dùng Việt Nam: Vai trò của sự hoài nghi về quảng cáo xanh và sự quan tâm đối với phúc lợi động vật - Nguyễn Viết, Bằng; Nguyễn Thị Lan, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study employs the SOR model to investigate the influence of consumer’s concern toward animal welfare and green advertising skepticism on Vietnamese consumers’ intention to engage in green purchasing. Data was collected from 386 consumers intending to go shopping green in Ho Chi Minh City. The study used Partial Least Squares Structural Equation Modeling (PLS-SEM) and Smart PLS software version 3.0 to analyze data. The findings of this study shed light on the relationship between concern for animal welfare and skepticism toward green advertising and the intention of green purchasing. The research has significant implications for the development of innovative marketing strategies aimed at target customers, especially for the Vietnamese market for green beauty care products